A Controlled Trajectory Rapid Compression and Expansion Machine (CT-RCEM) for Chemical Kinetic Investigations. Issue 9 (1st September 2020) - Tripathi, Abhinav; Sun, Zongxuan
ABSTRACT: In this work, we present a controlled trajectory rapid compression and expansion machine (CT-RCEM) for chemical kinetic investigations of fuels, with the unique capability of precise motion control of the piston in the combustion chamber. This capability allows the CT-RCEM to achieve a wider operating range and extreme flexibility of operation as changes in the piston trajectory are made electronically, unlike the conventional rapid compression machines (RCM) that require mechanical intervention. Also, precise motion control of the piston ensures high run-to-run repeatability of the piston trajectory, which in turn, naturally enables the CT-RCEM to achieve highly repeatable pressure and temperature profiles for compression and expansion over the entire operating range. The key novelty of CT-RCEM, however, lies in the new paradigm of experimental investigation that it provides for chemical kinetic studies. The thermodynamic path of the fuel mixture in the combustion chamber during an RCM investigation (essentially pressure and temperature history) is a function of the heat transfer characteristics of the chamber assembly as well as the piston trajectory. Hence, by suitable selection of the piston trajectory, the CT-RCEM allows not only the capability to set the end of compression thermodynamic state (compressed pressure and temperature), but also the flexibility to tailor the entire thermodynamic path, during and after the compression. In this paper, we demonstrate three novel research capabilities realized by tailoring the thermodynamic path – first, ability to systematically investigate the effect of changing the thermodynamic path of compression on the ignition delay of fuels for same end of compression pressure and temperature; second, ability to quench chemical reactions in the entire combustion chamber at any desired stage; and third, ability to investigate ignition delay of fuels for isobaric post-compression conditions by compensating the potential pressure drop due to heat loss with a unique creeping piston trajectory. We conclude with a discussion of the significance of these new research capabilities for chemical kinetic studies, especially autoignition investigations.